Pengaruh Bimbingan Orang Tua dan Kedisiplinan Belajar Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SD Negeri 79 Seluma - Yemi Heprianti (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This study aims: 1) To analyze how much influence parental guidance has on student achievement in Islamic Religious Education subjects at SD Negeri 79 Seluma. 2) To analyze how much influence learning discipline has on student achievement in Islamic Religious Education subjects at SD Negeri 79 Seluma. 3) To analyze the influence of parental guidance and learning discipline on student achievement in Islamic Religious Education subjects at SD Negeri 79 Seluma. This type of research uses quantitative research with an approach ex post facto. The population of this study amounted to 133 students, and the research sample amounted to 100 students. The sampling technique is the proportionate stratified random sampling technique. Data collection techniques using questionnaires, documentation and observation. The data analysis technique uses: multiple linear regression, t test, F test, coefficient of determination (R)2. The results show that: 1) There is an effect of parental guidance on student achievement in Islamic education subjects at SD Negeri 79 Seluma. This is seen based on the regression results, it is known that the Standardized Coefficients Beta X1  Y = 0,305 = 30,5% while the significance value (sig) is 0.003 < (  ) 0,05. 2) There is an influence of student learning discipline on student achievement in Islamic Religious Education subjects at SD Negeri 79 Seluma. This can be seen based on the regression results, it is known that the Standardized Coeffients Beta X2  Y = 0.260 = 26.0% with a significance value (sig) of 0.012 < (  ) 0.05. 3) There is an effect of parental guidance and learning discipline together on student achievement in Islamic Religious Education subjects at SD Negeri 79 Seluma. This is in accordance with the results of the joint regression coefficient test (F test) and the coefficient of determination test (R)2. Based on the calculation of statistical tests, the significant value of F arithmetic > F table is 15.133 > 3.090 with a significance level of 0.000 while the value of R square X 1.2  Y = 0.238 = 23.8%, then HOrejected , and Haaccepted.